Keanekaragaman Bivalvia di Kawasan Ekosistem Mangrove Desa Jeruju Besar Kalimantan Barat - Pangamiti, Floraria Maya; Helena, Shifa; Nurdiansyah, Syarif Irwan (Program Studi Ilmu Kelautan FMIPA Universitas Tanjungpura, 2025)
Bivalves are benthic organisms from the phyllum Mollusca phylum commonly found in mangrove ecosystems, particularly in areas with muddy or sandy substrates. These organisms play an essential role in maintaining ecosystem balance and serve as environmental bioindicators. This study aims to determine the composition, community structure, and environmental parameters that influence bivalve life in the mangrove ecosystem of Jeruju Besar Village, Sungai Kakap District, West Kalimantan. The research was conducted in December 2024 using a systematic method to determine sampling stationss, with a total of 3 stations. Each station has 3 subplots with a size of 1x1 m2 following the transect line which is placed parallel to a distance of 10m. Bivalve diversity in the mangrove ecosystem area of Jeruju Besar Village consists of 2 species, namely, Geloina expansa and Pharella acutidens. Density Station 1 has a density range (0-0.45 ind/m2), station 2 (0-2.28 ind/ m2), station 3 (0-1.64 ind/ m2). The diversity index (H') of bivalves ranged from (0.451-undefined), uniformity index (E') (0.693-undefined), and dominance index (C) (0.722- 1).